Analysis of SiBakul Jogja Regulations as a Strategy to Strengthen Micro and Small Enterprises - Agus, Yoga Mulya; Murwadji, Tarsisius; Mulyati, Etty (Damhil Law Journal, 2024)
This study aims to analyze the regulation of registration requirements as a seller in the Marketplace owned by the Regional Government in terms of the concept of MSE empowerment in Government Regulation Number 29 of 2021 concerning the Implementation of the Trade Sector and the regulation of commission fees in the Marketplace owned by the Regional Government in terms of the concept of MSE empowerment in Law Number 20 of 2008 concerning Micro, Small and Medium Enterprises (UMKM Law). The research method used in this research is normative legal research using a statutory approach. Based on the results of the research, two things can be concluded. First, Marketplace Si Bakul is in line with the concept of MSE Empowerment in Government Regulation Number 29 of 2021 concerning the Implementation of the Trade Sector, especially in Article 58. Second, the commission fee at Marketplace Si Bakul is different from the concept of MSE empowerment, as stated in Article 9 Letter B of the UMKM Law.